Analisis Pengelolaan dan Pemanfaatan Aset Wakaf di Kelurahan Mappala, Kecamatan Rappocini, Kota Makassar - Wardy Putra, Trisno; Zhafirah Ali, Muthia (Management of Zakat and Waqf Journal (MAZAWA), 2021)
The economic empowerment of the ummah to improve the standar of living of the community requires a professional waqf management system that has reliable human resources to improve and development the knowledge and also to improve nazhir ability to build strong, professional and responsible managerial skills. Existence nazhir very important in maintaining and managing the waqf. This study discusses how the empowerment and utilization of waqf assets carried out by nazhir. Nazhir efforts in developing endowment assets in the productive waqf.Furthemore, waqf nazhir strategy in emerging the standard of professionalism can be answered through the strengthening of institutional waqf, building nazhir capacity, developing managerial waqf and its functions that included in it. The research is qualitative in nature which is approached descriptively by showing the human interest side to solve the problem of waqf assets. the data was extracted through interviews and documentation, the data was validated by triangulation technique. The results of this study are 1) waqf land is only managed as a place of worship and education, it has no productivity value. 2) the resources they have come from what they are and do not have professional experience. Of course this is the main problem in the management of waqf assets.